PENYALAHGUNAAN POSISI DOMINAN DAN INTEGRASI VERTIKAL PADA PERUSAHAAN LAYANAN PENGIRIMAN YANG DILAKUKAN OLEH MARKETPLACE DALAM PERSPEKTIF HUKUM PERSAINGAN USAHA - Kurniawan, Satria; Setyawati, Ria; Wulandari, Sinar Aju (Program Studi Hukum Ekonomi Syariah, Universitas Hasyim Asy'ari, 2026)
The growth of the digital economy has brought about major transformations in trade transaction patterns, one of which is through online marketplace platforms. Within this digital ecosystem, some businesses have managed to secure a dominant position not only as platform providers but also through vertical integration of the supply chain, including logistics services. This study examines how vertical integration—specifically, direct ownership or control over the selection of logistics services utilized by marketplace businesses—influences user behavior, both among end consumers and merchants, in choosing logistics services. In practice, vertical integration is often implemented through algorithmic guidance, default settings for delivery options, price incentives, and restrictions on access to delivery data for external logistics providers. Such strategies pose the potential for abuse of dominant positions by suppressing independent delivery services through systematic, nontransparent preference mechanisms. The research methodology employed is a normative legal approach, involving an analysis of applicable laws and regulations, particularly Law No. 5 of 1999 on the Prohibition of Monopoly Practices and Unhealthy Business Competition, as well as a case study of vertical integration practices within large marketplace platforms in Indonesia. The findings indicate that the use of vertical integration in this context is not merely a matter of business efficiency but can lead to the exclusion of competitors and the unfair reduction of consumer choice, ultimately creating discrimination in the goods delivery services market.